CURRICULUM REFORM 2023: BETWEEN ADAPTATION AND CONTROVERSY - Loso Judijanto; Mustopa; Yadi Suryadi (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to evaluate the impact of the 2023 curriculum reform on the quality of learning in Indonesian schools. By adopting this reform, an improvement in the quality of learning covering students' cognitive, affective and psychomotor aspects is expected. This study critically examines how the implementation of the new curriculum may affect teachers' teaching methods, student participation, as well as overall learning outcomes. The study takes a multi-stakeholder perspective that includes opinions from teachers, students and parents to gain a comprehensive view of the reform. This study uses the literature research method, where data is collected through analyzing documents, journal articles and previous research reports related to the curriculum implemented in Indonesia and other countries for comparison. The results show that the 2023 curriculum reform has positive potential in improving the quality of learning in schools, both at primary and tertiary levels. The new curriculum learning system supports a more active and student-oriented learning style and enhances students' critical and creative skills. However, the biggest challenges relate to the readiness of school infrastructure and the professional development of teachers in implementing innovative teaching methods. In addition, student participation in the learning process is reported to be increasing, although there are concerns regarding access gaps especially in remote areas.